Lone star tarnished : a critical look at Texas politics and public policy - Jillson, Calvin C., 1949- (New York, NY : Routledge, 2021)
"Texas pride, like everything else in the state, is larger than life. So, too, perhaps, are the state's challenges. Lone Star Tarnished approaches public policy in the nation's most populous "red state" from historical, comparative, and critical perspectives. The historical perspective provides the scope for asking how various policy domains have developed in Texas history. In each chapter, Cal Jillson compares Texas public policy choices and results with those of other states and the United States in general. Finally, the critical perspective allows readers to question the balance of benefits and costs attendant to what is often referred to as "the Texas way" or "the Texas model" and to assess the many claims of Texas's exceptionalism. Through Jillson's lively and lucid prose, students are well equipped to analyse how Texas has done and is doing compared to selected states and the national average over time and today. This text is aimed at students and professors of Texas politics who want to stress history, political culture, and public policy"--
Part I: The great state of Texas? -- The Texas way -- Texas: the myth vs. the reality -- Demographic change and its implications -- Part II: The reality thus far -- Jobs, income, and wealth in Texas -- Public education in Texas -- Higher education in Texas -- Health and human services in Texas -- Crime and punishment in Texas -- Good roads, highways, and transportation in Texas -- Energy and the environment in Texas -- Part III: The coming reality -- The way forward.
OCLC-licensed vendor bibliographic record.
Keywords: Political planning -- Texas; Texas -- Politics and government; Texas -- Social policy; Texas -- Economic policy; POLITICAL SCIENCE / General